COMPLEX EVALUATION OF THE USE SYSTEM USED IN THE FIELD OF FIELD - Hospodarenko, H.; Prokopchuk, I.; Stasinіevуch, O.; Boіko, V. (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
In the article the calculation of the integrated assessment index (ICO) of the fertilizer system in the field crop rotation is considered, since it is believed that the most effective fertilizer system is that which provides the maximum increase in the crop yield of agricultural crops. From the economic point of view, this is not always feasible in the long run, as mineral fertilizer prices grow at a higher pace than crop production. Therefore, nowadays it is preferable to optimize the fertilizer system by a complex indicator that takes into account the level of crop yields, profitability and energy consumption of fertilizers. However, this approach does not take into account possible changes in soil fertility at different intensity levels of humus, nitrogen, phosphorus and potassium in crop rotation. The optimal and permissible values of individual indicators were determined taking into account the standard norms of return factors of nutrients from yielding and ecologically safe norms of the intensity of balance of phosphorus and potassium, depending on the content of their mobile compounds in the soil. In this approach, seven indicators were taken into account: payback of 1 kg of fertilizer of mineral fertilizers; additionally conditionally net profit; net energy income; the balance of humus and the intensity of the balance of nitrogen, phosphorus and potassium. On the basis of the conducted research, it was found that the lowest IQO fertilizer application in the field crop rotation was in the version of the experiment with the addition of nitrogen, nitrogen and potassium and phosphorus and potassium fertilizers – 1.14-1.20. This indicator was the highest in the experimental version N110P60K40 – 1.29. Somewhat inferior to the variants N110P60K80 and N110P30K40. Calculations show that the system of fertilizer application with the introduction of 1 hectare of crop rotation N110P30K40 temporarily, during two rotations of 4-way crop rotation, can be used in farms with insufficient financial support. However, taking into account agrochemical and energy efficiency and prospects for soil fertility restoration, the average annual rotation of crop rotation was the average annual N110P60K40 (ICO = 1,29).